Avaliação microestrutural e comportamento físico e mecânico de concretos de alto desempenho produzidos com metacaulim - Carlos Augusto de Souza Oliveira (2007)
Structure-property relationships represent the essence of the modern materials science. For concretes, materials with heterogeneous and complex structures, these relationships still are not well developed. The incorporation of different materials in its manufacture, such as pozzolans, has contributed, even more, the increase the complexity of its microstructure. The description of the structure of concretesmanufactured with pozzolans, is important in order to understand its performance. The metakaolin, aluminossilicate material obtained from the calcination of some types of clays such as kaolinitic clays and kaolin, is one of the materials that recently are being used as mineral admixture in the production of high-performance concretes. The majority of the studies carried out with this mineral admixture, evaluated only itsinfluence on the mechanical properties of concretes. In this work the microstructure of the concrete manufactured with metakaolin was evaluated. In this research, concrete was manufactured with 0, 10 and 15% cement replaced by metakaolin. The relationships between physical properties and microstructure of concretes were studied. The thermal analyses and of spectrometry in the infrared spectrometry data ofthe concrete showed that for the same water/agglomerate ration, the calcium hydroxide content reduced with the increase of metakaolin content in the concrete, being this behavior partially responsible for the improved physical behavior of the concrete manufactured with metacaulim when compared the reference concrete. In a generalway, the low water/agglomerate ration was foud to be a major cause of the physical similarity of the structure of the concretes. The reduction of the porosity and the average diameter of the pores of the concrete with the hidration evolution and with the cement content replaced by metakaolin had provided a refinement of the pore structureof the concrete. This contributed to densification of the microstructure, corroborating the improvements observed in the physical and microstructural properties of the concrete. The pH analyses showed that the metakaolin contents did not contribute for the armor corrosion phenomena. The results allow us to suggest that the use ofmetakaolin is technically viable in the production of concrete with high performance and durability.